2015
DOI: 10.1016/j.socscimed.2015.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood crime and depressive symptoms among African American women: Genetic moderation and epigenetic mediation of effects

Abstract: Introduction Social scientists have long recognized the important role that neighborhood crime can play in stress-related disease, but very little is known about potential biosocial mechanisms that may link the experience of living in high-crime neighborhoods with depression. Objective The current study introduces an integrated model that combines neighborhood, genetic, and epigenetic factors. Methods Hypotheses were tested with a sample of 99 African American women from the Family and Community Health Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 29 publications
3
44
0
Order By: Relevance
“…As hypothesized, long-term exposure to neighborhood disadvantage was related to chronic illness ( b = 0.203, IRR = 1.225, p =.004). The results are consistent with numerous studies (Aneshensel, 2009; Hill et al 2005; Lei et al, 2015; Ross & Mirowsky, 2001, 2009) reporting that residing in a disadvantaged neighborhood has a deleterious effect on physical health even after controlling for selection bias, socioeconomic status, and health-related behaviors.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As hypothesized, long-term exposure to neighborhood disadvantage was related to chronic illness ( b = 0.203, IRR = 1.225, p =.004). The results are consistent with numerous studies (Aneshensel, 2009; Hill et al 2005; Lei et al, 2015; Ross & Mirowsky, 2001, 2009) reporting that residing in a disadvantaged neighborhood has a deleterious effect on physical health even after controlling for selection bias, socioeconomic status, and health-related behaviors.…”
Section: Resultssupporting
confidence: 90%
“…However, while individuals living in disadvantaged neighborhoods are more likely to become ill than those residing in more advantaged areas, many, if not most, will remain healthy (Fone et al, 2007; Lei et al, 2015; Miller et al, 2011), a phenomenon labeled “neighborhood resilience” (Brody, Yu, Beach, 2016b; Masten & Coatsworth, 1998; Norris et al, 2008). This raises the question: Why and how do some people living in disadvantaged neighborhoods develop chronic illnesses whereas others do not?…”
Section: Resilience Mechanisms In Neighborhoodsmentioning
confidence: 99%
“…Short allele carriers exposed to early life stress were more likely to display increased 5-HTT gene methylation than homozygous long allele carriers in a sample of 105 young adults [52]. Consistent with this finding, short allele carriers that have grown up in dangerous neighborhoods show greater methylation than long allele carriers [53]. This association conferred a significant risk for depressive symptoms in this sample.…”
Section: -Htt Gene Methylationsupporting
confidence: 67%
“… 18 Previous studies have demonstrated a link between global or site-specific DNA methylation patterns and socially patterned stressors including low childhood SES, 1-4 low adult SES, 3 , 4 perceived stress, 2 and neighborhood crime. 19 Differential DNA methylation patterns have also been demonstrated for a wide variety of physical and mental health indicators (e.g., cardiovascular disease, 20 inflammation, 21 cortisol levels, 2 and depression.) 22 In light of these associations, DNA methylation has been proposed as a mediator of the associations between social exposures and health.…”
Section: Introductionmentioning
confidence: 99%